IMPLEMENTASI TEORI KEPEMIMPINAN MICHIGAN OLEH WAKA KESISWAAN DALAM MENDUKUNG KEDISIPLINAN SISWA DI SMP ISLAM SHAFTA SURABAYA - Al Arifin, Rifi Rohmatul Minan; Abdurrohman Hanifah Al-Fajr; Nur Ainiyah; MINAN, Sania Tri Wahyuni; Adinda Islamatul Nur Aziza; Erny Roesminingsih (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The success of educational institutions is not solely determined by the principal's leadership, but also by strategic-level leaders such as the Vice Principal for Student Affairs (Waka Kesiswaan). This study aimed to describe the implementation of the Michigan Leadership Theory by the Waka Kesiswaan of SMP Islam Shafta Surabaya, encompassing two main dimensions: production-centered and employee-centered orientations. A descriptive qualitative approach was employed, with data collected through passive participatory observation and semi-structured in-depth interviews. The sole informant was the Waka Kesiswaan of SMP Islam Shafta Surabaya, the only official holding the position. The findings indicate that the Waka Kesiswaan implements both leadership orientations in a balanced and integrative manner. The production-centered orientation is reflected in the strict application of disciplinary standard operating procedures, a violation point system, and oversight of student program achievements. Meanwhile, the employee-centered orientation is evident in the emotional approach toward students, open communication, confidentiality of student information, and cross-role collaboration with school counselors and the principal. The integration of both orientations yielded significant positive impacts on character formation, student discipline, trust, psychological well-being, and learning effectiveness. This study concludes that effective school leadership is one that integrates firmness in task management with warmth in building relationships, as formulated in the Michigan Leadership Theory.